(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
In future biomass are planned as main source as renewable energy. The grain and straw are as one of the representatives of biomass. During 2007 - 2008 in the State Stende Cereal Breeding Institute the investigations were carried out to define more accurately spring cereal–wheat, barley and oats for heat production. In the field experiment were sown 4 - 6 varieties from each species. The yield, chemical composition, the highest and lowest heating capacity of grain and straw were evaluated. The highest heating capacity for grain was 15475 - 16994 and the lowest – 13828 - 15356 kJ kg-1; in straw – 15788 - 16840 and 14106 - 15230 kJ kg-1respectively. Accordingly to this value the cereal species arranged in the following order: oats, barley and wheat. The varieties of cereal were differed in heating capacity depending on chemical composition. Significant positive correlation was observed between grain heating capacity and fat (r = 0.993; r0.01 = 0.684), and fiber (r= 0.838; r0.01 = 0.684), but significant negative correlation with starch (r = - 0.847; r0.01 = 0.684).